Aerodynamic Analysis of Micro Aerial Vehicle Rotor Blade at Low Reynolds Number - Kamruzzaman, Md.; Nepal, Sushil; Arafa, Mushfiq Al (Asian Journal of Engineering and Applied Technology, 2021)
The numerical simulation of micro aerial vehicle (MAV) rotor blade aerodynamics is highly challenging in the field of rotor aerodynamics. The aim of this paper is to present a computational fluid dynamics (CFD) study on the aerodynamics analysis of micro aerial vehicle rotor blade at low-Reynolds number by means of Spalart-Allmaras turbulence model. The KA152313 airfoil, which is dedicated to mid to small-scale rotorcraft, e.g. MAV is chosen to design the rotor blade. The rotor blade was investigated in three different pitch configurations, which are GP13º, GP12º and GP11º and the aerodynamics characteristics are analyzed respectively. The CFD results of the analysis is used to compare the aerodynamic characteristics, e.g. pressure force, shear force and pitching moment on the chord surface of the rotor blades at different pitch configurations.